PENGARUH APLIKASI KOMPOS KULIT BUAH KOPI TERHADAP KANDUNGAN BAHAN ORGANIK DAN FOSFOR PADA INCEPTISOL KEBUN KOPI DESA BANGELAN, MALANG - Nadiya Risdawati; S Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
High coffee production rates result in an increase in coffee waste, especially on the skin, which has not been used optimally. Inside the skin of the coffee fruit, there is 45.3% organic matter, 2.98% nitrogen, 0.18% phosphorus, and 2.26% potassium content which has the potential to be used as compost. The soil used in this research is Inceptisol soil type obtained from PTPN XII Bangelan Coffee Plantation, Malang. Inceptisol soil in this land has several problems, such as low soil fertility due to intensive use and improper fertilizer management. The use of compost can increase nutrient content and increase the pH value of the soil. This research was done in three different places at PTPN XII Bangelan for taking samples, Agriculture Faculty of Brawijaya University, especially in Soil Biology and Chemistry Laboratory for the incubation process and analysis of soil chemical characteristics. This research used a completely randomized factorial design with nine treatments and three replications. The nine treatments consisted of different soil depth such as (0 - 20 cm, 20 - 40 cm, and 40 - 60 cm) and three different dosages. The results showed that the application of coffee peel residue to soil significantly affected organic matters (organic-C) and phosphorus. For organic matters, soil depth that consisted most of it was 0 – 20 cm (topsoil), and the fertilizer dosage that consisted most of it was dosage 0.58 g ha-1 and 1.16 g ha-1.